Preparation method of multicolor long afterglow material based on Sr3Y2Ge3O12 matrix

By doping Bi3+, Bi2+ and Mn2+ ions in the Sr3Y2Ge3O12 matrix, optimizing process parameters, and preparing high-brightness, multi-color long afterglow materials, the shortcomings of existing materials in luminescence intensity, chemical stability and luminescence color are solved, and applications in the fields of indicator lighting, anti-counterfeiting markings and building inspection are realized.

CN120519161APending Publication Date: 2025-08-22NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510624019.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-08-22

AI Technical Summary

Technical Problem

Existing long afterglow materials have shortcomings in luminous intensity, chemical stability and luminous color, which limits their application range.

Method used

By doping Bi3+, Bi2+ and Mn2+ ions into the Sr3Y2Ge3O12 matrix, the process parameters are optimized, and high-brightness, multi-color long afterglow materials are prepared, suitable for indicator lighting, anti-counterfeiting markings and building inspections.

Benefits of technology

The prepared materials exhibit bright blue or red afterglow under ultraviolet excitation, have good chemical stability and high-intensity afterglow characteristics, and are suitable for a variety of practical application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120519161A_ABST
    Figure CN120519161A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multicolor long afterglow material based on a Sr3Y2Ge3O12 matrix, and belongs to a preparation technology of a long afterglow material. According to the method, by doping different ions Bi < 3 + >, Bi < 2 + > and Mn < 2 + >, the luminescent characteristic of the long-afterglow material in various colors is realized, and the luminescent property of the material is improved by optimizing process parameters. The preparation method comprises the following specific preparation steps: preparing raw materials, grinding and mixing, adding a rheological agent and a dispersing agent, defoaming, adsorbing, drying and calcining. The prepared long-afterglow material has good chemical stability and high-strength afterglow characteristic, and can be applied to the fields of luminous paint for indicating illumination, printing ink for anti-counterfeiting marks, penetrating fluid for fluorescent flaw detection and the like, and the fields of mechanoluminescent films for building structure detection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation technology of long afterglow materials, in particular to a method based on Sr3Y2Ge3O 12 The invention relates to a method for preparing a multi-color long afterglow material of a matrix. Background Art

[0002] Long-afterglow materials are a special class of luminescent materials that can continue to emit light for a period of time after the excitation light source has stopped. Their luminescence mechanism is that after the material absorbs light energy, electrons are excited to a higher energy state, and then release light energy through an electronic transition process.

[0003] Currently, research on long-lasting glow materials primarily focuses on three major systems: sulfides, aluminates, and silicates. Although sulfide-based long-lasting glow materials have been studied earlier, they suffer from low luminescence intensity and poor chemical stability, limiting their application. Aluminate-based long-lasting glow materials offer high stability and cost advantages, but they suffer from a single luminescence color and poor water resistance. Silicate-based long-lasting glow materials offer a moderate bandgap and good synthesis and storage properties, but their luminescence efficiency still needs to be further improved.

[0004] In recent years, compounds with garnet structure (A3B2X3O 12 Among them, A=Ca, Sr, B=Y, Ga, In, Sc, Al and X=Si, Ge, etc.) have attracted attention due to their unique structural advantages, such as Y3Ga5O 12 ,Ca3Ga2Ge3O 12 Sr3Y2Ge3O has been considered as a good host lattice material with afterglow characteristics. 12 The octahedral voids and dodecahedral voids in the base long afterglow material structure are more conducive to ion doping, which can produce more effective traps and thus emit high-intensity afterglow. 12 It also has good chemical and thermal stability and is considered to be an ideal long afterglow material matrix.

[0005] The present invention aims to study Sr3Y2Ge3O 12 Based on long afterglow materials, and systematically studied different doping ions (Bi 3+ 、Bi 2+ 、Mn 2+ ) on the material structure and luminescence properties, and then developed a Sr3Y2Ge3O 12 The preparation method of the high-brightness, multi-color long-afterglow material of the matrix can be applied to the fields of luminescent coatings for indicator lighting, printing inks for anti-counterfeiting labels, penetrants for fluorescent flaw detection, and mechanoluminescent films for building structure inspection. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for preparing a high-brightness, multi-color long-afterglow material, which realizes the luminescence characteristics of multiple colors by doping with different ions, and optimizes the process parameters to improve the luminescence performance of the material.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] A Sr3Y2Ge3O-based 12 The preparation method of the high brightness, multi-color and long afterglow material of the matrix specifically comprises the following steps:

[0009] S1. Weigh the raw materials GeO2, SrCO3 and Y2O3 according to the molar ratio of each element; the molar ratio of each element is Sr:Y:Ge:O=3:2:3:12, and the required doping ion Mn is used. 2+ Or Bi 3+ / Bi 2+ , weigh MnCO3 or Bi2O3, Mn 2+ The molar ratio of doping elements is 0.03-0.05 or Bi 3+ / Bi 2+ During doping, the molar ratio of the doping elements is 0.005-0.01.

[0010] S2. Grinding and mixing: Grind the S1 raw material using water as a medium.

[0011] S3. Add rheological agent and dispersant to the mixed solution in S2 and continue grinding.

[0012] S4. Add defoaming agent to the mixed solution in S3 and grind until a uniform white slurry is obtained.

[0013] S5. Immerse the pretreated organic support in the S4 slurry and adsorb for 15 minutes, repeating 5 times.

[0014] S6. After the organic carrier adsorbs the slurry, it is dried and placed in a muffle furnace for calcination.

[0015] S7, after calcination, naturally cool to room temperature to obtain Sr3Y2Ge3O 12 Multi-color long-lasting glow material.

[0016] Preferably, the method for preparing a high-brightness, multi-color long-afterglow material is characterized in that the fineness of each raw material is 200 mesh.

[0017] Preferably, the grinding is performed using a stirring mill, and the rotation speed of the stirring mill is set to 1000 r / min.

[0018] Preferably, the rheological agent is a 2 wt% polyvinyl alcohol (PVA) aqueous solution, and its usage accounts for 1 wt% of the total mass of the raw materials.

[0019] Preferably, the dispersant is a 6 wt % polyethylene glycol (PEG) aqueous solution, and its usage accounts for 2 wt % of the total mass of the raw materials.

[0020] Preferably, the defoaming agent is ethanol, which is added dropwise into the mixed solution, and the amount of ethanol used accounts for 6wt% of the total mass of the raw materials.

[0021] Preferably, the organic carrier in S5 is polyurethane foam, and its pretreatment process is: first, the organic carrier is placed in a 5 mol / L NaOH solution, soaked at 50°C for 3 hours, and repeatedly rubbed with clean water to clean it; then placed in a PVA aqueous solution with a mass fraction of 16 wt%, soaked at 60°C for 4 hours, repeatedly rubbed with clean water to clean it, and dried at room temperature.

[0022] Preferably, the drying system of the organic carrier in S6 is to dry it naturally for 24 hours and then dry it in an oven at 60° C. for 10 hours to remove moisture.

[0023] Preferably, the calcination conditions are air atmosphere or reducing atmosphere-carbon powder: at room temperature-300°C, the heating rate is 5°C / min, and the temperature is kept for 2 hours; at 300°C-900°C, the heating rate is 1°C / min, and at 900°C-1250°C, the heating rate is 5°C / min, and the temperature is kept for 3 hours.

[0024] Beneficial effects of the present invention: the doping ion is Bi 3+ When the material is doped with Bi 2+ When doped with Mn ions, the material emits red light; 2+ When the material is heated, it emits bright red light with obvious afterglow effect. The prepared long afterglow material has good chemical stability and high-intensity afterglow characteristics, and can be used in luminescent coatings for indicator lighting, printing inks for anti-counterfeiting labels, penetrants for fluorescent flaw detection, and mechanoluminescent films for building structure detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments:

[0026] Figure 1 XRD patterns of samples prepared with the ratios (1) to (3) of Example 1 of the present invention;

[0027] Figure 2 The CIE chromaticity diagram of the sample prepared by the ratio (2) of Example 1 of the present invention;

[0028] Figure 3 This is a three-dimensional afterglow image of the sample prepared with the ratio (2) of Example 1 of the present invention;

[0029] Figure 4 This is the emission spectrum of the sample prepared with the ratio (2) of Example 1 of the present invention;

[0030] Figure 5 This is the afterglow decay curve of the sample prepared with the ratio (2) of Example 1 of the present invention;

[0031] Figure 6 The CIE chromaticity diagram of the sample prepared by the ratio (2) of Example 2 of the present invention;

[0032] Figure 7 This is a three-dimensional afterglow image of the sample prepared with the ratio (2) of Example 2 of the present invention;

[0033] Figure 8 The CIE chromaticity diagram of the sample prepared according to the ratio (1) of Example 3 of the present invention;

[0034] Figure 9 This is a three-dimensional afterglow image of the sample prepared with the ratio (1) of Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below with reference to the accompanying drawings in the embodiments of the present invention.

[0036] Example 1

[0037] Select SrCO3, Y2O3, GeO2, and MnCO3 as the starting compound raw materials. According to the molar ratio of each element, weigh four compound raw materials respectively, a total of 3 groups, with the following ratios:

[0038] (1) Sr:Y:Ge:O:Mn=3:2:3:12:0.03, corresponding to x=3.00%;

[0039] (2) Sr:Y:Ge:O:Mn=3:2:3:12:0.04, corresponding to x=4.00%;

[0040] (3) Sr:Y:Ge:O:Mn=3:2:3:12:0.05, corresponding to x=5.00%.

[0041] The weighed raw materials were mixed with water at a mass ratio of 100:150, and ground for 20 minutes using water as the medium. The speed of the stirred mill was set to 1000r / min. After grinding, a rheological agent and a dispersant were added to the mixture. The rheological agent was a 2wt% polyvinyl alcohol (PVA) aqueous solution, accounting for 1wt% of the total mass of the raw materials. The dispersant was a 6wt% polyethylene glycol (PEG) aqueous solution, accounting for 2wt% of the total mass of the raw materials. The stirred mill was continued to grind for 20 minutes to fully disperse the rheological agent and dispersant in the slurry. Subsequently, the defoaming agent ethanol was added dropwise, accounting for 6wt% of the total mass of the raw materials, and the grinding was continued until a uniform white slurry was obtained.

[0042] The pretreated polyurethane foam was immersed in the slurry and adsorbed under vacuum conditions for 15 minutes, repeated 5 times. The polyurethane foam after adsorption of the slurry was naturally dried for 24 hours, and then dried in an oven at 60°C for 10 hours to remove moisture. The dried polyurethane foam was placed in a muffle furnace and calcined in a reducing atmosphere (carbon powder). The calcination conditions were: room temperature to 300°C, heating rate of 5°C / min, holding temperature for 2 hours; 300°C to 900°C, heating rate of 1°C / min; 900°C to 1150°C, heating rate of 5°C / min, holding temperature for 3 hours.

[0043] After calcination, it was cooled naturally to room temperature to obtain Sr3Y2Ge3O 12 :xMn 2+ This long afterglow material emits red light after being excited by ultraviolet light, and has a significant afterglow effect, making it suitable for a variety of practical applications.

[0044] Figure 1 Sr3Y2Ge3O 12 :xMn 2+ The comparison of X-ray powder diffraction pattern of long afterglow sample and standard diffraction card pattern. From the XRD pattern, we can see that the prepared sample is similar to Sr3Y2Ge3O 12 The results showed that the product was matched with the standard card PDF#85-2410, which verified the successful synthesis of the target product.

[0045] Figure 2 For the preparation of Sr3Y2Ge3O 12 :4%Mn 2+ The CIE chromaticity diagram of long-lasting materials shows that the material exhibits red afterglow.

[0046] Figure 3 For the preparation of Sr3Y2Ge3O 12 :4%Mn 2+ The three-dimensional afterglow diagram of long-afterglow materials shows the attenuation trend of afterglow intensity in different bands.

[0047] Figure 4The fluorescence emission spectra produced by X-ray and UV-260nm excitation are shown in Figure 2. 12 :4%Mn 2+ It can be efficiently excited by X-rays and also produces fluorescence emission at 469nm.

[0048] Figure 5 Sr3Y2Ge3O 12 :4%Mn 2+ The afterglow attenuation curve of the long afterglow material shows that the sample has good afterglow characteristics and the afterglow time exceeds 16 hours.

[0049] Example 2

[0050] Select SrCO3, Y2O3, GeO2, and Bi2O3 as the starting compound raw materials. According to the molar ratio of each element, weigh four compound raw materials respectively, a total of 3 groups, with the following ratios:

[0051] (1) Sr:Y:Ge:O:Bi=3:2:3:12:0.005, corresponding to x=0.50%;

[0052] (2) Sr:Y:Ge:O:Bi=3:2:3:12:0.0075, corresponding to x=0.75%;

[0053] (3) Sr:Y:Ge:O:Bi=3:2:3:12:0.01, corresponding to x=1.00%.

[0054] The weighed raw materials were mixed with water at a mass ratio of 100:150, and ground for 20 minutes using water as the medium. The speed of the stirred mill was set to 1000r / min. After grinding, a rheological agent and a dispersant were added to the mixture. The rheological agent was a 2wt% polyvinyl alcohol (PVA) aqueous solution, accounting for 1wt% of the total mass of the raw materials. The dispersant was a 6wt% polyethylene glycol (PEG) aqueous solution, accounting for 2wt% of the total mass of the raw materials. The stirred mill was continued to grind for 20 minutes to fully disperse the rheological agent and dispersant in the slurry. Subsequently, the defoaming agent ethanol was added dropwise, accounting for 6wt% of the total mass of the raw materials, and the grinding was continued until a uniform white slurry was obtained.

[0055] The pretreated polyurethane foam was immersed in the slurry and adsorbed under vacuum for 15 minutes, repeated five times. The polyurethane foam after adsorption was allowed to air dry for 24 hours and then dried in an oven at 60°C for 10 hours to remove moisture. The dried polyurethane foam was then calcined in an air muffle furnace under the following conditions: room temperature to 300°C at a heating rate of 5°C / min, holding for 2 hours; 300°C to 900°C at a heating rate of 1°C / min; and 900°C to 1250°C at a heating rate of 5°C / min, holding for 3 hours.

[0056] After calcination, it was cooled naturally to room temperature to obtain Sr3Y2Ge3O 12 :xBi 3+ Long afterglow material. This material emits bright blue light when excited by ultraviolet light.

[0057] Figure 6 For the preparation of Sr3Y2Ge3O 12 : 0.75% Bi 3+ The CIE chromaticity diagram of long-lasting materials shows that the material exhibits blue afterglow.

[0058] Figure 7 For the preparation of Sr3Y2Ge3O 12 : 0.75% Bi 3+ The three-dimensional afterglow diagram of long-afterglow materials shows the attenuation trend of afterglow intensity in different bands.

[0059] Example 3

[0060] Select SrCO3, Y2O3, GeO2, and Bi2O3 as the starting compound raw materials. According to the molar ratio of each element, weigh four compound raw materials respectively, a total of 3 groups, with the following ratios:

[0061] (1) Sr:Y:Ge:O:Bi=3:2:3:12:0.005, corresponding to x=0.50%;

[0062] (2) Sr:Y:Ge:O:Bi=3:2:3:12:0.0075, corresponding to x=0.75%;

[0063] (3) Sr:Y:Ge:O:Bi=3:2:3:12:0.01, corresponding to x=1.00%.

[0064] The weighed raw materials were mixed with water at a mass ratio of 100:150, and ground for 20 minutes using water as the medium. The speed of the stirred mill was set to 1000r / min. After grinding, a rheological agent and a dispersant were added to the mixture. The rheological agent was a 2wt% polyvinyl alcohol (PVA) aqueous solution, accounting for 1wt% of the total mass of the raw materials. The dispersant was a 6wt% polyethylene glycol (PEG) aqueous solution, accounting for 2wt% of the total mass of the raw materials. The stirred mill was continued to grind for 20 minutes to fully disperse the rheological agent and dispersant in the slurry. Subsequently, the defoaming agent ethanol was added dropwise, accounting for 6wt% of the total mass of the raw materials, and the grinding was continued until a uniform white slurry was obtained.

[0065] The pretreated polyurethane foam was immersed in the slurry and adsorbed under vacuum conditions for 15 minutes, repeated 5 times. The polyurethane foam after adsorption of the slurry was naturally dried for 24 hours, and then dried in an oven at 60°C for 10 hours to remove moisture. The dried polyurethane foam was placed in a muffle furnace and calcined in a reducing atmosphere (carbon powder). The calcination conditions were: room temperature to 300°C, heating rate of 5°C / min, holding temperature for 2 hours; 300°C to 900°C, heating rate of 1°C / min; 900°C to 1150°C, heating rate of 5°C / min, holding temperature for 3 hours.

[0066] After calcination, it was cooled naturally to room temperature to obtain Sr3Y2Ge3O 12 :xBi 2+ Long afterglow materials.

[0067] Figure 8 For the preparation of Sr3Y2Ge3O 12 : 0.5% Bi 2+ The CIE chromaticity diagram of long-lasting materials shows that the material exhibits red afterglow.

[0068] Figure 9 For the preparation of Sr3Y2Ge3O 12 : 0.5% Bi 2+ The three-dimensional afterglow diagram of long-afterglow materials shows the attenuation trend of afterglow intensity in different bands.

[0069] The present invention demonstrates the efficiency and flexibility of preparing multicolor long-lasting glow materials through examples. It should be noted that the above examples are intended only to illustrate the core principles of the present invention and are not exhaustive. Those skilled in the art can adjust and optimize the synthesis conditions, raw material ratios, and process parameters based on this specification to meet the needs of different applications. The scope of protection of the present invention shall be determined by the claims and their equivalents.

Claims

1. A Sr3Y2Ge3O-based 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The following steps are involved: S1. Weigh the raw materials GeO2, SrCO3 and Y2O3 according to the molar ratio of each element; the molar ratio of each element is Sr:Y:Ge:O=3:2:3:12, and the required doping ion Mn is used. 2+ Or Bi 3+ / Bi 2+ , weigh MnCO3 or Bi2O3, Mn 2+ The molar ratio of doping elements is 0.03-0.05 or Bi 3+ / Bi 2+ The molar ratio of the doping elements during doping is 0.005-0.01; S2, grinding and mixing: grinding the S1 raw material with water as the medium; S3, adding rheological agent and dispersant to the mixed solution in S2, and continuing grinding; S4. Add defoamer to the mixed solution in S3 and grind until a uniform white slurry is obtained; S5, immersing the pretreated organic support into the S4 slurry, adsorbing for 15 minutes, repeating 5 times; S6, drying the organic support after adsorption of the slurry and placing it in a muffle furnace for calcination; S7, cooling: After the calcination is completed, it is naturally cooled to room temperature to obtain Sr3Y2Ge3O 12 Multi-color long-lasting glow material.

2. A method based on Sr3Y2Ge3O according to claim 1 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The fineness of each raw material in step S1 is 200 mesh.

3. A method based on Sr3Y2Ge3O according to claim 1 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The grinding is performed using a stirring mill, and the rotation speed of the stirring mill is set to 1000 r / min.

4. A method based on Sr3Y2Ge3O according to claim 1 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The rheological agent is a 2 wt % polyvinyl alcohol (PVA) aqueous solution, and its usage accounts for 1 wt % of the total mass of the raw materials.

5. The Sr3Y2Ge3O-based 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The dispersant is a 6 wt % polyethylene glycol (PEG) aqueous solution, and its usage accounts for 2 wt % of the total mass of the raw materials.

6. The Sr3Y2Ge3O-based 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The defoaming agent is ethanol, which is added dropwise into the mixed solution, and the amount of ethanol used accounts for 6wt% of the total mass of the raw materials.

7. The Sr3Y2Ge3O-based 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The organic carrier in S5 is polyurethane foam, and its pretreatment process is as follows: first, the polyurethane foam is placed in a 5 mol / L NaOH solution, immersed at 50°C for 3 hours, and repeatedly rubbed with clean water to clean it; then, it is placed in a PVA aqueous solution with a mass fraction of 16 wt%, immersed at 60°C for 4 hours, repeatedly rubbed with clean water to clean it, and dried at room temperature.

8. The Sr3Y2Ge3O-based 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The drying system of the organic carrier after adsorption of the slurry is to dry it naturally for 24 hours and then dry it in an oven at 60° C. for 10 hours to remove moisture.

9. The Sr3Y2Ge3O-based 12 The method for preparing a multi-color long afterglow material of a matrix is ​​characterized in that: The calcination conditions are as follows: the temperature is raised at a rate of 5°C / min from room temperature to 300°C and the temperature is kept at this temperature for 2 hours; the temperature is raised at a rate of 1°C / min from 300°C to 900°C and at a rate of 5°C / min from 900°C to 1250°C and the temperature is kept at this temperature for 3 hours.